Opinion journalism in Peru news of femicide. Solsiret Rodríguez case - Anticona Alegre, Angie Jennifer (2023)
Currently, at the Latin American level, feminist collectives, such as Me too or Ni una menos, are gaining more and more notoriety in the media and social networks. This is largely due to the large amount of news, where the woman stands out for being the victim of sexual, psychological and physical abuse. It should be noted that many of these cases remain unresolved or forgotten. For this reason, every day there are more people who, outraged by this situation, find it necessary to raise their voices in protest with the intention of imparting justice and defending women's rights. Precisely, one way to express your point of view is through the written word. This study proposes to analyze and compare four opinion columns from the web platform of the newspaper Perú 21, written by Peruvian public figures who belong to the political and journalism sector, about the femicide of Solsiret Rodríguez, a young Peruvian and activist from Not one less, who was murdered by her brother-in-law, Kevin Alexander, and by his partner: Andrea Aguirre. The research level is descriptive-comparative, qualitative and non-experimental. The content analysis technique is used and its instrument is the analysis matrix. The population is equal to the sample: four columns of opinion.